Aggravation of climate change crisis in Gulf Regions of United States: A Review of Anthropogenic Factors - Damoah, Benjamin; Adu , Emmanuel; Ofori , Eunice; Apraku, Amos (Journal of Ecohumanism, 2024)
The Gulf Coast of the United States is increasingly at risk from the impacts of climate change, exacerbated by various human-induced factors. This review paper examined how human activities have worsened the effects of climate change in this region from 2005 to 2024, which is already vulnerable to hurricanes, sea-level rise, and coastal erosion. Key factors include intensive industrial operations, such as oil and gas production, which release significant amounts of greenhouse gases and disrupt the natural landscape, leading to land subsidence and weakening coastal defenses. Urbanization and population growth have resulted in the loss of valuable wetlands and other natural buffers that mitigate flooding and storm surges. Alterations to river systems for flood control and navigation have reduced sediment deposition; thereby affecting the preservation of coastal landforms. Agricultural practices in the region also play a key role; fertilizer and pesticide runoff contaminate waterways and create hypoxic zones, negatively impacting fisheries and marine habitats. This paper emphasizes the need for impactful policy interventions and sustainable behaviors to address these human-induced pressures. The paper also advocates a comprehensive mitigation strategy including stricter emission controls, financial support for renewable energy sources, habitat restoration, and improved urban planning to enhance climate change resilience. After conducting a thorough review, we have discovered that the Gulf Coast region has experienced over fifteen deadly hurricanes over the past twenty years alone and is poised to confront increasingly complex environmental and socioeconomic challenges if viable solutions are not implemented. These issues can potentially jeopardize the livelihoods of the region's inhabitants and the health of its diverse ecosystems.